Teoretyczny model doskonałości dla obszarów przyrodniczo cennych - Zielińska, Anetta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The excellent model of nature protected areas will create a coherent system of space and function protection of nature. It is focused on achieving some changing in governing of protected areas. Building such a model depends on following requirements: - suitable legal, organizational, economical and dimensional mechanisms; - coordination of interdisciplinary actions for nature protection on the area of the whole country; - applying tools fixing ecological economy; - applying monitoring system for nature protection and applying index controlling system; - planning nature protection in 20 years ahead; - building ecological education system. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 57-64